Treatment of hypertension in old patients without previous cardiovascular disease. Issue 11 (November 2019) - Bager, Johan-Emil; Hjerpe, Per; Manhem, Karin; Björck, Staffan; Franzén, Stefan; Rosengren, Annika; Adamsson Eryd, Samuel
Abstract : Objective: The aim of this study was to compare the risk of cardiovascular disease (CVD) – nonfatal acute myocardial infarction (AMI) or stroke – at blood pressure levels that meet current recommendations with risk at lower levels, particularly in older patients. Methods: We identified patients with hypertension aged 40–90 years from a primary care register. Patients with a history of cancer, diabetes mellitus or CVD were excluded. Patients were divided into age groups (40–75 and 76–90), and four groups of SBP 110–129, 130–139 (reference), 140–149 and ≥150 mmHg. We used the Kaplan–Meier estimator to study incidence of AMI, stroke and a composite of the two. Cox proportional-hazards regression was used to estimate hazard ratios for outcomes. Results: We included 31 704 patients: 26 663 were 40–75 years old and 5041 were 76–90 years old. Mean follow-up was 2 years. Although no significant differences in risk of any outcome were found in the younger group, low blood pressure was associated with the lowest risk in the older group. Older patients in the 110–129 mmHg group had a lower incidence of CVD (15.9/1000 vs. 25.3/1000 person-years) than the reference group. After adjustment for covariates, the hazard ratio of CVD in older patients in the 110–129 mmHg group compared with the reference group was 0.60 (95% confidence interval 0.40–0.92). Conclusion: Blood pressure levels lower than those currently recommended are not harmful among older patients. The association between lower SBP and lesser risk of CVD may instead suggest a beneficial effect of lower SBP. Abstract : Supplemental Digital Content is available in the text